Patent quality and trade credit: Based on the perspective of knowledge breadth - Yihan Li; Man Wang (PLoS ONE, 2025)
Firms often rely on their own unique knowledge to obtain profits, but the reproducibility of knowledge will weaken economic interests, so firms adopt patents to establish exclusivity to clarify the ownership of profit rights. However, patents are only a form, and what kind of knowledge is contained behind them is the key to whether a firm can obtain and how much economic benefit it can obtain. In order to protect intellectual property rights in an all-round way, firms often hold a lots of patents, forming a patent matrix containing multiple cross-knowledge. The more complex the knowledge connotation of the patent matrix, the more difficult it is to be imitated, and the better the protection benefits of patents, forming high-quality patents. This study selects China’s A-share listed companies from 2006 to 2023 as the sample, utilizes patent acquisition data of listed firms, and measures corporate patent quality from the perspective of knowledge breadth—the wider the knowledge breadth embedded in patents, the higher the patent quality. Based on this framework, this study investigates how patent quality, measured by knowledge breadth, influences firms’ access to trade credit. The findings reveal that improvements in corporate patent quality significantly enhance access to trade credit access, with this effect being more pronounced among non-state-owned enterprises and firms in patent-intensive industries. Further analysis demonstrates that patent quality facilitates trade credit access by strengthening bargaining power and elevating corporate reputation. This research not only clarifies the mechanism that ultimately reinforces the operationalization of innovation-driven development frameworks by enhancing firms’ technological competitiveness and market credibility, but also enriches the channels through which patents influence corporate financing, and provides policy recommendations to advance patent quality development. These findings enable firms to leverage patent assets in reducing transaction costs and financing burdens.